Attribute based feature recognition for machining features - Abu, Risal; Md. Tap, Masine (Penerbit UTM Press, 2007)
Automated feature recognition is considered a critical component for integration of CAD/CAPP/CAM. The automation of process planning requires the implementation of a feature recognition procedure, so that decisions relating to steps of process planning activities can be made. Various methodologies have been developed to automate feature recognition. This paper presents an approach to feature recognition using rule based on different characteristics specific to each feature such as the total number of faces, the total number of edges, the type of faces, and the attribute of feature i.e. protrusion/depression. The proposed method is implemented using Graphics Interactive Programming (GRIP) and Unigraphics solid modeler. The results show that the proposed technique is capable of recognizing features with a unique set of attributes. The rule is also simple, easy to understand and implement.